Relationship Between Galvanic Vestibular-evoked Myogenic Potentials and the Prognosis of Unilateral Severe to Profound Idiopathic Sudden Sensorineural Hearing Loss With Vertigo. Issue 7 (August 2021) - Chang, Chih-Ming; Lo, Wu-Chia; Young, Yi-Ho; Liao, Li-Jen; Cheng, Po-Wen
Abstract : Objective: Idiopathic sudden sensorineural hearing loss (ISSNHL) may not only impair cochlear function but also damage vestibular structures, including the saccule, utricle, semicircular canals, and vestibular afferents. Poor recovery often occurs in patient with serious ISSNHL and accompanying vertigo. To define the severity of the disease and to predict prognosis, galvanic vestibular-evoked myogenic potentials (VEMPs) are added to the inner ear test battery. Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Thirty patients with unilateral severe to profound ISSNHL and accompanying vertigo were enrolled in this retrospective study. Intervention: Diagnostic. Main Outcome Measures: All subjects underwent pure tone audiometry, cervical and ocular VEMPs, and caloric tests before the initiation of treatment. The treatment outcome, rates of abnormal responses in the tests, and the characteristic parameters of VEMPs such as latencies and amplitudes, were analyzed. Results: In affected ears, the rates of abnormal acoustic cVEMPs, vibratory oVEMPs, galvanic cVEMPs, and galvanic oVEMPs were 60, 47, 37, and 20%, respectively. The improvement in the hearing of the affected ear was specified as good recovery or poor recovery. The normal galvanic VEMP group had a significant higher rate of good recovery than abnormal galvanic VEMP group (87% versus 27%; p  = 0.003). Conclusions: Patients with unilateral severe to profound ISSNHL and accompanying vertigo who have normal galvanic VEMPs have a higher likelihood of hearing recovery than those who have abnormal galvanic VEMPs.